Rediscovering life after being diagnosed with HIV: A qualitative analysis of lived experiences of youth living with HIV in rural Rwanda - Uwamariya, Josée; Nshunguyabahizi, Marcel; Nshimyumuremyi, Jean Népomuscène; Mukesharurema, Gerardine; Ndayishimiye, Emmanuel; Kamali, Innocent; Ndahimana, Jean d’Amour; Hedt-Gauthier, Bethany; Cubaka, Vincent K.; Barnhart, Dale A. (Frontiers in Reproductive Health, 2022)
Introduction In sub-Saharan Africa, youth living with HIV, especially those who have lost one or both parents, face economic, socially and psychological challenges that hinder adherence to ART, ultimately leading to poor health outcomes. Partners In Health/Inshuti Mu Buzima implemented an Adolescent Support Group (ASG) to support HIV-positive youth aged 15–25 years. During the evaluation of the ASG program, we sought to better understand youths' lived experiences to improve our delivery of HIV care. Methods We conducted qualitative in-depth, semi-structured individual interviews with youth enrolled in the ASG program. All interviews were conducted in-person or by telephone. Thematic analysis applying the framework approach with parallel inductive coding in Kinyarwanda and English was used. Results We interviewed 35 youth who ranged in age from 16 to 29 years. The main themes related to the lived experiences of youth were (a) Experiences living with HIV, including disclosure, stigma, interactions with the health care system, and medication adherence; (b) external challenges, defined as challenges that were not related to the implementation of the ASG program; and (c) personal vision. Almost all youth reported acquiring HIV from their mothers and disclosure of HIV status occurred around the age of 10. Disclosure was often unintentional and followed by internalized and enacted stigma. Many reported poor past medication adherence which improved following enhanced counselling. External challenges were overwhelmingly economic in nature, and orphanhood was a root cause of other challenges such as difficulty accessing education, lack of transport to health facility, and lack of insurance fees. Despite these challenges, youth have an optimistic view of the future with dreams of health, economic attainment, marriage, and children. Conclusion Healthcare providers should empower caregivers to support HIV disclosure. Supporting youth as they face many economic challenges could help address socio-economic barriers to good health and promote holistic well-being.